Concomitant outbreaks of yellow fever and hepatitis E virus in Darfur States, Sudan, 2012 - Sarah S Ahmed; Mohammed A Soghaier; Sozan Mohammed; Hayat S Khogali; Muntasir M Osman; Abdalla M Abdalla (Journal of Infection in Developing Countries)
Introduction: Yellow fever (YF) is a vector-borne disease transmitted to humans by infected Aedes mosquitoes, while hepatitis E virus (HEV) is a waterborne disease that is transmitted through the fecal-oral route. Both diseases have very close clinical presentation, namely fever, jaundice, malaise, and dark urine; they differ in severity and outcome. Methodology: In this cross-sectional, laboratory-based study, an attempt was made to measure the correlation of concomitant YF and HEV infection in Darfur States during the previous YF outbreak in 2012. Results: Results found concomitant outbreaks of YF and HEV at the same time with very weak statistical correlation between the two infections during the outbreak period, with Cramer’s V correlation 0.05 and insignificant p value of 0.86. Conclusions: This correlation indicates that clinicians and care providers in tropical areas have to deal with clinical case definitions used for disease surveillance very carefully since prevalence of HEV infection is relatively common and this increases the possibility of misclassification and missing YF  cases, particularly initial index cases, in a season or outbreak.